Analysis of the Effect of Porosity on the Acoustic and Elastic Properties of Materials Using Ultrasonic Immersion Pulse-Echo Technique - Maiyena, Sri; Mat Daud, Anis Nazihah; Ayop, Shahrul Kadri (Jurnal Fisika dan Aplikasinya, 2024)
The material properties is an important aspect in determining the potential application of a material. Hence, this study is carried out to determine the effect of porosity on the material properties (acoustic properties and elastic properties) of material using the pulse echo immersion ultrasonic technique. This study comprises of two acoustic properties (longitudinal velocity and acoustic impedance) and five elastic properties (Young's modulus, shear modulus, bulk modulus, longitudinal modulus and Lamé constant). Two types of PMMA samples are used for this study; nonporous sample and porous sample. The result indicated that the material properties (acoustic properties and elastic properties) of porous sample are less than the material properties of non-porous sample. It indicated that the porosity gives significant effect towards the material properties.